2014
DOI: 10.1007/s13277-014-2631-4
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 promotes the proliferation and metastasis of osteosarcoma cells by activating the PI3K/Akt pathway

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), one of the first found cancer-associated long noncoding RNAs (lncRNAs), involves in the development and progression of many types of tumors. An aberrant expression of MALAT1 was observed in hepatocellular carcinoma, cervical cancer, breast cancer, ovarian cancer, and colorectal cancer. However, the exact effects and molecular mechanisms of MALAT1 in osteosarcoma progression are still unknown up to now. Here, we investigated the role of MALAT1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
228
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(237 citation statements)
references
References 26 publications
9
228
0
Order By: Relevance
“…MALAT1 is an evolutionarily conserved lncRNA that does not undergo translation into protein (16). Nevertheless, previous findings suggest that MALAT1 regulates the alternative splicing of pre-mRNAs by controlling the expression of serine/arginine splicing factors, while also having a key role in tumorigenesis (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MALAT1 is an evolutionarily conserved lncRNA that does not undergo translation into protein (16). Nevertheless, previous findings suggest that MALAT1 regulates the alternative splicing of pre-mRNAs by controlling the expression of serine/arginine splicing factors, while also having a key role in tumorigenesis (27).…”
Section: Discussionmentioning
confidence: 99%
“…To date, evidence demonstrates that MALAT1 plays a key role in the progression of various cancers, including cervical cancer (15), osteosarcoma (16), breast cancer (17) and colorectal cancer (18). However, the expression and function of MALAT1 are currently unknown in OC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that lncRNAs may exert different effects in osteosarcoma. Metastasis-associated lung adenocarcinoma transcript 1 was reported to promote the proliferation and metastasis of osteosarcoma cells (30). Downregulation of taurine upregulated 1 inhibited osteosarcoma cell proliferation and promoted apoptosis (31).…”
Section: A B C D Discussionmentioning
confidence: 99%
“…As one of the first identified cancer-associated lncRNAs, MALAT1 contributes to the pathogenesis of many types of tumors, including hepatocellular carcinoma, cervical cancer, breast cancer, ovarian cancer, and colorectal cancer [26] . MALAT1 knockdown has suppressed the proliferation and the invasion of human osteosarcoma cell and inhibited its metastasis potential.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%